Test Consumer Acceptance Of Processed Products Jackfruit seed sampler (Arthocarphus heterophillus) as Cassava Substitution - Andriani; Akbar. H. Anr, Riyadlul (TAPE : Jurnal Teknologi Hasil Pertanian, 2024)
Jackfruit (Artocarpus heterophyllus), is one of the tropical fruits that is widely grown in Asia, including Indonesia. Jackfruit seeds are one of the by-products of jackfruit that are often obtained in the food processing process that uses jackfruit asthe main ingredient. Such as jackfruit chips and dodol. Jackfruit seeds are rarely used and known to the public. The use of jackfruit seeds is only limited to seeds, animal feed, boiled, burned or roasted. The use of jackfruit seeds has high nutritional value. Kepeng or commonly called samiler (cassava) is a type of traditional food that has long been consumed by the people of Indonesia from various walks of life. In this study, cassava, which is the main ingredient in making kepeng, was replaced with jackfruit seeds. This study aims to determine the acceptability of jackfruit seed kepeng. The method used in testing acceptability is an organoleptic test which is processed using the Kruskal Wallis test. The results of the research were based on analysis of data obtained from the organoleptic test panelists' assessment of jackfruit seed samples which had differences in color, taste, aroma and kepeng texture. The results of the Kruskal Wallis test on the color parameter show a value of 0.01<0.05 so it can be said that H is rejected or there is a significant difference, the taste test results show a significant value of 0.03<0.05 so it can be said that H is rejected or there is a difference which is significant, the results of the aroma test show a significant value of 0.313>0.05 so it can be said that H is accepted or there is no difference, and the results of the Kruskal test on texture parameters show a significant value of 0.161<0.05 so it can be said that H is accepted or there is no difference.